2012
DOI: 10.1021/om300414y
|View full text |Cite
|
Sign up to set email alerts
|

Fischer Dinuclear and Mononuclear Bis-Carbene Complexes of Thiophene and Thiophene Derivatives

Abstract: The reaction of dilithiated thiophene and thiophene derivatives with group 6 transition metal carbonyl precursors and subsequent alkylation afforded linearly arranged Fischer 2,5-bis-carbene and the rare unsymmetrical 2,3-bis-carbene chelated complexes. The latter requires a second lithiation to occur at an adjacent, less reactive site on the thiophene ring. The control of reactivity sites was investigated and achieved by either blocking more reactive positions with substituents or activating less reactive pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 75 publications
(184 reference statements)
1
4
0
Order By: Relevance
“…Notably no monocarbene complexes, with the carbene carbon in a β-position, were isolated while using n-BuLi. This is in line with our previous studies showing that lithium-halogen exchange is a requirement for β-carbon lithiation under the reaction conditions employed [12,19].…”
Section: Synthesis and Characterization Of Monocarbene Complexessupporting
confidence: 93%
See 2 more Smart Citations
“…Notably no monocarbene complexes, with the carbene carbon in a β-position, were isolated while using n-BuLi. This is in line with our previous studies showing that lithium-halogen exchange is a requirement for β-carbon lithiation under the reaction conditions employed [12,19].…”
Section: Synthesis and Characterization Of Monocarbene Complexessupporting
confidence: 93%
“…The complexes with the carbene moiety in the C5-position represent a more linear (open) arrangement for the dithienyl and ethoxy substituents of the carbene ligand. In 2a, 2b, 4a and 4b the ethoxy substituents point towards the sulphur atom of the adjacent thienyl ring, which is the electronically favoured conformation [6,7,19]. However for the aminolysed complex (7a), the nitrogen atom is on the opposite side of the thienylene sulphur atom; emphasizing the electronic and steric differences between an amino-and an ethoxycarbene substituent in Fischer carbene complexes.…”
Section: Scheme 2 Aminolysis Of Mono-ethoxycarbene Complexesmentioning
confidence: 97%
See 1 more Smart Citation
“…The detailed synthesis and characterization of most of the complexes of this study have been reported previously [13][14][15][16][17][18][19][20]. Complex (5) was synthesized according to the analogous methoxy complex reported in literature [13] and characterization data are similar.…”
Section: Synthesis Characterisation and X-ray Crystallographymentioning
confidence: 99%
“…43 Using another approach, chelated biscarbene complexes of chromium and tungsten could be formed upon consecutive CO functionalizations. 44 3-Bromo-5-methyl-thiophene was deprotonated by LDA and reacted with M(CO) 6 to form a 2-carbeniate. Subsequent Li/Br exchange with n-BuLi effected a second nucleophilic attack on a cis-positioned CO ligand, and alkylation yielded the product (Scheme 3).…”
Section: ð2þmentioning
confidence: 99%